Pengetahuan dan Sikap Ibu dalam Pemberian Jajanan Sehat pada Anak di Taman Kanak –Kanak Baiturrahim Jambi - Iin Indrawati; Faridah Faridah (Universitas Baiturrahim, 2021)
Children's food consumption is usually influenced by how conditions are in their household, mothers have an important role in teaching, selecting and even modeling the food and snacks they consume. The research objective was to find out how the influence of health education with emotional demonstration techniques on the knowledge and attitudes of mothers in providing healthy snacks to children at Baiturrahim Kindergarten Jambi.This research is a quantitative study with a quasi-experimental design. The population of this study was 23 mothers whose children attended TK Baiturrahim and the sample technique chosen was total sampling.Maternal knowledge before the intervention was good 16 people (68.7%), poor 7 people (31.3%) and after the intervention was good 21 people (91.3%), less good 2 people (8.7%) ). As for the attitude variable, it was found that 19 people were good (80.7%), 4 people were not good (19.3%) and after the intervention was good 21 people (90.7), 2 people poor (9.3) . The results of the bivariate analysis showed that health education with emotional demonstration techniques had a significant effect on maternal knowledge with a value of P = 0.000, and for attitudes also showed significant results with a value of P = 0.032.Health education with emotional demonstration techniques needs to be introduced to the community, and regular planning needs to be made by involving all related parties so that they can work together to achieve the goals of a smart and healthy society